Highly Secure and Easy to Remember Password-Based Authentication Approach - Sayed Elham Sadat; Hedayatullah Lodin; Nazak Ahmadzai (Journal of Social Science Utilizing Technology, 2024)
Background. Everyone connected and using the Internet is concerned regarding the security and also the privacy of their sensitive information available on the Internet. As authentication is the fundamental part of security, there are different authentication mechanisms through which the systems can be secured. The password-based authentication mechanism is a cheap and easy method for enforcing authentication in the systems for many years. The weakest aspect in password security is human, as they choose weak and easy to guess passwords or a highly secure and complex password which might be difficult to remember and recover the password. Purpose. In this paper, a password generation system is proposed which generates a password based on the user’s input like, time and location data. The system generates a password that is highly secure, easy to remember, easy to recover, and can effectively defend against Brute force and dictionary attacks. Method. This study utilizes a descriptive quantitative approach to develop a password-based authentication system focused on security and memorability. The population includes digital users needing secure access, with samples drawn from various groups to ensure comprehensive feedback. Data collection involves password strength evaluation tools and user feedback questionnaires. Procedures include developing a password generation algorithm using user inputs, followed by testing its security and conducting usability assessments. Feedback will guide the refinement of the system to enhance user experience and security. Results. The generated passwords using the porposed system have been checked in three online password checkers, which verifies that the system is generating highly secure and crack resistant passwords and the method for recovering the forgotten password was efficient and easy. The system is implemented using PHP scripting language with a user-friendly environment. Conclusion. This paper proposes a password-based authentication system that generates secure and memorable passwords using user input, time, and location data. The passwords were validated through three online checkers, demonstrating high security and resistance to attacks. Future enhancements could include voice recognition to improve security and personalization, making the system more user-friendly while maintaining low costs.